(Un)drawing Belgium's colonial monuments: Comics' engagement with decolonial debates. (December 2021) - Bragard, Véronique; Lambert, Alicia
As a response to the debates around colonial statues and glorifying forms of memorialization, comics provide one with plurivocal possibilities to decolonize monuments and epistemologies. This article analyzes a number of recent comics/panels (Charles & Bihel, Stassen, Kannemeyer, Baruti, Lambé, a.o.) that de-center perspectives so as to visibilize the violence of the Belgian colonial system that public monuments invisibilize. This analysis focuses on the medium-specific features that depetrify (in)famous statues, draw back to iconic figures like the Leopard-Man, and redraw iconic sites with multilayered temporalities and geographies to enable viewers to move away from one-sided perspectives and consider present forms of discriminations as legacies of colonialism.